Truth. - Engel, Pascal (Taylor and Francis, 2014)
In this critical introduction to contemporary philosophical issues in the theory of truth Pascal Engel provides clear and authoritative exposition of recent and current ideas while providing original perspectives that advances discussion of the key issues. This book begins with a presentation of the classical conceptions of truth - the correspondence theory, the coherence theory and verificationist and pragmatist accounts - before examining so-called minimalist and deflationist conceptions that deny truth can be anything more than a thin concept holding no metaphysical weight. The debates betw.